2022
DOI: 10.3389/fcvm.2022.817453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Novel Pocket Compression Device on Hematomas Following Cardiac Electronic Device Implantation in Patients Receiving Direct Oral Anticoagulants

Abstract: BackgroundA pocket hematoma is a well-recognized complication that occurs after pacemaker or defibrillator implantation. It is associated with increased pocket infection and hospital stay. Patients suffering from atrial fibrillation and undergoing cardiovascular electronic implantable device (CIED) surgery are widely prescribed and treated with direct oral anticoagulants (DOACs). In this study, the use of a novel compression device was evaluated to examine its ability to decrease the incidence of pocket hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Our research demonstrated that mortality rates were higher among NOAC and P2Y12 inhibitor users. The fact that P2Y12 inhibitors are more potent agents than ASA and the difficulty in finding the antidote for NOACs may have caused an increase in all-cause mortality 14 . Cardiac conditions commonly co-occur with chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Our research demonstrated that mortality rates were higher among NOAC and P2Y12 inhibitor users. The fact that P2Y12 inhibitors are more potent agents than ASA and the difficulty in finding the antidote for NOACs may have caused an increase in all-cause mortality 14 . Cardiac conditions commonly co-occur with chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical compression devices have also been designed to be applied after wound closure. Some of these devices have demonstrated benefit in reducing postoperative hematoma [94][95][96]. Pressure dressings may be used for 24 hours although their efficacy has not been demonstrated.…”
Section: Wound Carementioning
confidence: 99%